The Influence of Family Guidance and Teacher PAK Professional Competence on the Effectiveness of PAK Subject in Class - Magdalena Sinaga; Dapot Damanik; Elisamark Sitopu (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to know and analyze the influence of family guidance on students' effectiveness in learning Christian education, professional competence on students' effectiveness in learning Christian education and determine the influence of family guidance and the professional competence of Christian education teachers on students' effectiveness in learning Christian education. This research uses descriptive and inferential quantitative methods. The population of this study was 212 people with a sample of 66 people taken randomly. The research instrument is a closed questionnaire, which was prepared by the researcher based on research variable indicators. There is a positive and significant influence between the professional competence of Christian education teachers on students' effectiveness in learning Christian education of 53.29% with Fcount > Ftable, namely 42.97 > 4.08. 3). There is a positive and significant influence between family guidance and the professional competence of teachers together on student effectiveness in learning Christian education by 57.45% with Fcount > Ftable, namely 42.77 > 3.15, with the regression equation Ŷ= 6, 85 + 0.27 X1 + 0.55 X2 thus Ho is rejected and Ha is accepted.